IDENTIFIKASI EKTOPARASIT PADA IKAN KOI (CYPRINUS RUBROFUSCUS) HASIL BUDIDAYA: Identification Of Ectoparasites In Cultured Koi Fish (Cyprinus rubrofuscus) - Hidayanti, Nurul; Sumahiradewi, Luh Gede; Aminullah, Aminullah (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
Koi fish (Cyprinus rubrofuscus) are ornamental fish with high economic value, but their cultivation is constrained by the supply of quality seeds. Poor aquatic environments and high fish density can cause parasitic infections that weaken immunity and cause stress and infection in fish. This study aims to determine the types of parasites, prevalence, intensity and dominance that attack koi fish. This study used a survey method. The primary data taken were the total length and weight of the fish, the type and number of parasites, and water quality (temperature, pH, DO and ammonia). The koi fish used were the result of self-cultivation at Andar Fish Farm Lingsar as many as 20 samples. The results showed 3 types of parasites found attacking koi fish samples, namely Dactyrogirus sp., Argulus sp., and Oodinium sp. The prevalence rate of parasites found attacking koi fish samples from the four sampling ponds ranged from 20 - 100%, falling into the category of frequent infections to always infections, then the level of parasite intensity found ranged from 1 - 16.4 individuals/tail with a low to moderate category, then the level of parasite dominance was 98.2% Dactyrogirus sp., 1.3% Argulus sp. and 0.44% respectively. Oodinium sp.